2002
DOI: 10.1016/s0092-8674(02)00676-1
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Control of Blood Cell Migration by the Drosophila VEGF Pathway

Abstract: We show that a vascular endothelial growth factor (VEGF) pathway controls embryonic migrations of blood cells (hemocytes) in Drosophila. The VEGF receptor homolog is expressed in hemocytes, and three VEGF homologs are expressed along hemocyte migration routes. A receptor mutation arrests progression of blood cell movement. Mutations in Vegf17E or Vegf27Cb have no effect, but simultaneous inactivation of all three Vegf genes phenocopied the receptor mutant, and ectopic expression of Vegf27Cb redirected migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
295
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(318 citation statements)
references
References 39 publications
21
295
0
2
Order By: Relevance
“…Mammalian hematopoietic cells and Drosophila prohemocytes use PDGF and VEGF pathways to direct the migration of cells during development and the immune response (Duchek et al, 2001). In Drosophila, a gene for a PDGF/VEGF receptor homolog (PVR, CG8222) and three ligands (Pvf1-3, CG7103, CG13780 and CG34378) were identified, characterized and implicated in the embryonic migration of hemocytes (Cho et al, 2002). Furthermore, Munier et al (2002) showed the expression of PVR on the surface of prohemocytes and circulating plasmatocytes.…”
Section: Drosophilamentioning
confidence: 99%
“…Mammalian hematopoietic cells and Drosophila prohemocytes use PDGF and VEGF pathways to direct the migration of cells during development and the immune response (Duchek et al, 2001). In Drosophila, a gene for a PDGF/VEGF receptor homolog (PVR, CG8222) and three ligands (Pvf1-3, CG7103, CG13780 and CG34378) were identified, characterized and implicated in the embryonic migration of hemocytes (Cho et al, 2002). Furthermore, Munier et al (2002) showed the expression of PVR on the surface of prohemocytes and circulating plasmatocytes.…”
Section: Drosophilamentioning
confidence: 99%
“…Embryonic plasmatocytes migrate along predetermined routes until the whole embryo is populated by stage 17 (39). For the plasmatocytes to migrate out of the head region, they require the activity of the Drosophila PDGF/VEGF receptor, Pvr and three ligands Pvf1, Pvf2, and Pvf3 (29). When the Pvr receptor or all three ligands are removed, the plasmatocytes fail to migrate out of the head region (29, 31).…”
Section: Wound Healingmentioning
confidence: 99%
“…The ligands Pvf1, Pvf2, and Pvf3 are redundant for hemocyte migration out of the head region. Furthermore, ectopic expression of one of the Pvr ligands, Pvr2, induces a chemotactic response in embryonic plasmatocytes (29). More recently, it was shown that the small GTPases Rac1, Rac2, and Cdc42 are also required for proper plasmatocyte migration during embryogenesis (40).…”
Section: Wound Healingmentioning
confidence: 99%
“…Similarly, the AML-1, is necessary for crystal cell development during embryonic and larval hematopoiesis (Daga et al 1996; Drosophila platelet-derived growth factor and VEGFreceptor-related (PVR) protein is expressed in hemo- Lebestky et al 2000). lz has been shown to function downstream of srp; however, additional interactions becytes and is required for the proper migration (Heino et al 2001;Cho et al 2002) and survival (Brü ckner et tween these transcription factors initiate hemocyte commitment to the crystal cell lineage (Fossett et al 2003;al. 2004) and mapped by the Drosophila Genome Project, cov-…”
Section: Espite the Obvious Differences In Cell Type And Cells And mentioning
confidence: 99%